Genetic Manipulation of Ticks: A Paradigm Shift in Tick and Tick-Borne Diseases Research - Nuss, Andrew; Sharma, Arvind; Gulia-Nuss, Monika (Frontiers in Cellular and Infection Microbiology, 2021)
Ticks are obligate hematophagous arthropods that are distributed worldwide and are one of the most important vectors of pathogens affecting humans and animals. Despite the growing burden of tick-borne diseases, research on ticks has lagged behind other arthropod vectors, such as mosquitoes. This is largely because of challenges in applying functional genomics and genetic tools to the idiosyncrasies unique to tick biology, particularly techniques for stable genetic transformations. CRISPR-Cas9 is transforming non-model organism research; however, successful germline editing has yet to be accomplished in ticks. Here, we review the ancillary methods needed for transgenic tick development and the use of CRISPR/Cas9, the most promising gene-editing approach, for tick genetic transformation.